Strategy to Strengthen the Implementation of Humanitarian Law Education for Members of the Indonesian National Army (TNI) - Arip Supriyadi; Riyandi; Tarsisius Susilo; Aqsha Erlangga; Iwan Setiawan (International Research and Development for Human Beings (IRDH), 2025)
Knowledge of humanitarian law plays a very important role for TNI members in the execution of their duties. The aim of this research is to identify the strengths, weaknesses, threats, and opportunities in humanitarian law education for TNI members, as well as to formulate strategies for enhancing humanitarian law education for TNI members. This research employs a qualitative method, with data analysis using a two-way comparison, namely Systematic Literature Review and SWOT Analysis. The research findings indicate that there are 5 strength factors, 5 weakness factors, 5 opportunity factors, and 5 threat factors in strengthening humanitarian law education for TNI members. The biggest strength factor is that humanitarian law education for TNI members has a strong legal basis, namely Law Number 59 of 1958 and Regulation of the Minister of Defense of the Republic of Indonesia Number 09 of 2013, while the biggest weakness factor is the lack of discussion between civil society, the government, and the military about humanitarian law. The biggest opportunity factor is that the space for cooperation between law enforcement agencies, universities, and the TNI is still open in terms of the implementation of humanitarian law education for TNI members, while the biggest threat factor is that humanitarian law is rarely the main topic in the study of national defense. There are 8 strategies to strengthen humanitarian law education for TNI members, namely strengthening the study of the implementation of humanitarian law in the learning curriculum, opening a space for study and discussion on the implementation of humanitarian law, opening a space for cooperation with international institutions that pay attention to international humanitarian law education, and giving aspirations to the House of Representatives of the Republic of Indonesia to update the Law on the implementation of law humanitarianism, opening a collaborative space for writing reference books on humanitarian law, designing a national defense and security system that is integrated with the internet of things and artificial intelligence, encouraging the Government of the Republic of Indonesia to take a strategic role as a pioneer in the implementation of humanitarian law, and providing protection and support to TNI members in the implementation of humanitarian law.